An analysis of the factors of NAIRU dynamics in selected OECD countries - Marjanović, Gordana; Mihajlović, Vladimir (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
Unemployment represents one of the major problems in modern economies. In order to create appropriate measures for its reduction, it is necessary to know the exact relationship between the NAIRU (Non-Accelerating Inflation Rate of Unemployment) and the actual unemployment rate. Therefore, this paper examines the impact of various factors on change in the NAIRU rate using the example of selected OECD countries. The impact of the actual unemployment rate on the NAIRU is analyzed by examining the presence of hysteresis in unemployment rates, while the second part of the analysis examines the impact of the longterm unemployment rate and trade union density on the NAIRU. The results show that the hysteresis hypothesis is confirmed in almost all the countries when the analysis is applied to the individual, but not to the panel data. On the other hand, changes in the rate of the long term unemployed explain a high percentage of change in the NAIRU, while the impact of the trade union density varies considerably from country to country. The main conclusion is that institutional reforms, which affect the labour market and especially the sources of long-term unemployment, might be successful in the reduction of unemployment rate and its fluctuations
Argument Oeconomica, 2016, Nr 1 (36), s. 87-103
Keywords: NAIRU; hysteresis; long-term unemployment; trade union density